Dignidade da pessoa humana e economia humanista: desafios da globalização e das novas tecnologias - Brezolin, Julia (2024)
This dissertation is part of the research line "Constitutional Jurisdiction and Democracy" with a concentration area in New Paradigms of Law, of the Master's degree in Law of the Stricto Sensu Graduate Program of the University of Passo Fundo. The objective of the research is to analyze the limits and possibilities of the Humanist Economy being used as a mechanism to reduce social inequalities and preserve the Dignity of the Human Person in a Latin American and global context. To this end, the dissertation was structured in three chapters. The first is intended to provide a historical review of the construction of the notion of Dignity and the establishment of a concept applicable in the scope of research. It also analyzes its recognition in declarations and constitutions in the Latin American and global context, as well as the challenges to implement the Right to Development and reduce inequalities. The second chapter aims to study the transformations of the economic system and the main impacts of the Industrial Revolutions, globalization and new technologies, on the transformations of capital and the establishment of an unproductive capitalism, considering the possibility of the Dignity of the Human Person being used as a paradigm for a humanistic and sustainable economic bias. The third and final chapter aims to examine humanist philosophy, especially that of economic law, the concept of humanist economics, and the possibility of implementing this system as an instrument for reducing social inequalities and preserving human dignity in the Latin American and global context. Thus, the research problem can be summarized in the following question: To what extent can humanist economics be used as an instrument for preserving human dignity in the face of the challenges of globalization and new technologies? To answer the problem, the deductive approach method was used, allowing us to move from general ideas to specific conclusions. The authors Ingo Wolfgang Sarlet, Ladislau Dowbor, Leonardo Boff, Ricardo Sayeg, Wagner Balera, among others, were used as the Basic Theory. As an investigative procedure, qualitative bibliographic research was used. Finally, as a result of the research, it was identified that the humanistic economy is viable and that, based on the Dignity of the Human Person, it enables the realization of human and fundamental rights, the rights of nature and full and sustainable human development. Furthermore, with this economic bias, the responsibility of companies towards society and the need for the State to resume its governance are restored. The themes addressed in the research are linked to the UN Sustainable Development Goals, especially the eradication of poverty (SDG 1), decent work and economic growth (SDG 8), industry, innovation and infrastructure (SDG 9), reduction of inequalities (SDG 10), sustainable cities and communities (SDG 11), sustainable consumption and production (SDG 12) and peace, justice and effective institutions (SDG 16).